IMPLEMENTASI TUGAS DAN WEWENANG MAJELIS RAKYAT PAPUA MENURUT UNDANG-UNDANG NOMOR 21 TAHUN 2001 TENTANG OTONOMI KHUSUS PAPUA - Anggun Putri Priyani (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2020)
Abstract This research intended to know the implementation of task and obligation of MRP obediently to the mandate of the law Number 21 of 2001 on Special Autonomy for Papua Province. This research did intended to know the protection of MRP to the basic righs of Papua indigenous, and the factors that influence the MRP in carrying out its duties and authority.This research was conducted by tracing the regulation and various literatures that has relation to this writing and interview with some source person of gaining input in order to perfecting this thesis writing.In order to implement special autonomy in Papua, it was formed MRP that is a the cultural representative of Papua indigenous, that has certain authority in the pace of protecting the Papua indigenous’ right, underlying to the esteem to the esteem to the custom and culture, female outsourcing, and the consolidation of religious life concordance. The results of this research showed that : 1) The implementation of the tasks and obligation of the MRP have not been conducted conseguently and consistently. The result, MRP has not fully give protection to the basic right of Papua indegenous. 2) the slowness of Provincial Government and DPRP in forming special regional regulation that rule on operational technique of the implementation of task and obligation of MRP and some duties and autorities of MRP that is amended in the article 20 paragraph (1) in Law Number 21 of 2001 on Special Autonomy to Papua Province, there are only (2) that could be implemented,i.e. the consideration and approval toward the candidate of Governor and Vice Governor nominees that was proposed by DPRP, and consideration and approval of MRP to the special regional regulation that was formed by Governor along with DPRP.Keywords: Special Autonomy, Papua Society Council (MRP), Right Of Papua Indigeous.AbstrakPenelitian bertujuan untuk mengetahui impelmentasi tugas dan wewenang MRP sesuai amanat Undang-Undang Nomor 21 Tahun 2001 Tentang Otonomi Khusus bagi Provinsi Papua. Penelitian ini juga bertujuan mengetahui perlindungan MRP terhadap hak-hak dasar orang asli Papua. Faktor-faktor yang mempengaruhi MRP dalam melaksanakan tugas dan wewenangnya. Penelitian ini dilakukan dengan cara menelusuri peraturan perundang-undangan dan berbagai literature yang ada kaitannya dengan penulisan tesis ini, dan wawancara dengan beberapa narasumber untuk mendapatkan masukan guna penyempurnaan penulisan tesis ini.Dalam rangka penyelenggaraan otonomi khusus di Papua dibentuk Majelis Rakyat Papua yang merupakan representasi kultural orang asli Papua, yang memiliki wewenang pada penghormatan terhadap adat dan budaya,pemberdayaan perempuan,dan pemantapan kerukunan hidup beragama.Hasil penelitian ini menunjukkan bahwa : 1) Implementasi tugas dan wewenang MRP belum dapat dilaksanakan secara konsekuen dan konsisten. Akibatnya MRP belum sepenuhnya memberikan perlindungan terhadap hak-hak dasar orang asli Papua.2) lambatnya Pemerintah Provinsi dan DPRP membentuk perdasus yang mengatur teknis operasional dalam pelaksanaan tugas dan wewenang MRP yang diamanatkan pada pasal 20 ayat (1) Undang-Undang Nomor 21 Tahun 2001 tentang Otonomi Khusus Bagi Provinsi Papua, ayat (2) yang dapat dilaksanakan yaitu pertimbangan dan persetujuan terhadap bakal calon Gubernur dan Wakil Gubernur yang diusulkan oleh DPRP, dan pertimbangan dan persetujuan MRP terhadap perdasus yang dibentuk oleh Gubernur bersama DPRP.Kata Kunci : Otonomi Khusus , Majelis Rakyat Papua, Hak-hak Orang Asli Papua.